2021
DOI: 10.1186/s40359-021-00515-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping strategies and expectations among breast cancer survivors in China: a qualitative study

Abstract: Background Breast cancer is a common tumor in China and has become a public health problem in modern society. Stress plays an important role in the occurrence and progression of cancer. At present, the current situation of stress on breast cancer survivors (BCSs) in China has not been fully understood. This study aims to explore the stress and coping strategies of Chinese BCSs, which provide suggestions to help BCSs reduce stress. Methods Sixty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…It follows that avoidant coping strategies and factors may be interpreted as either adaptive or maladaptive on individual basis as they can also contribute to fostering short-term adjustments to surgery. Indeed, combined approach-avoidant coping consisting of both supportive and goal-oriented strategies appears to be more effective in lowering surgery-related distress, consistent with recent studies claiming that breast cancer patients can feel unburdened through self-regulation and help from others [ 58 , 62 ]. However, extensive use of avoidant strategies could also reveal the tendency to focus on external circumstances beyond one’s perceived control, entailing an increased risk for developing mental health issues over time [ 63 ].…”
Section: Discussionsupporting
confidence: 77%
“…It follows that avoidant coping strategies and factors may be interpreted as either adaptive or maladaptive on individual basis as they can also contribute to fostering short-term adjustments to surgery. Indeed, combined approach-avoidant coping consisting of both supportive and goal-oriented strategies appears to be more effective in lowering surgery-related distress, consistent with recent studies claiming that breast cancer patients can feel unburdened through self-regulation and help from others [ 58 , 62 ]. However, extensive use of avoidant strategies could also reveal the tendency to focus on external circumstances beyond one’s perceived control, entailing an increased risk for developing mental health issues over time [ 63 ].…”
Section: Discussionsupporting
confidence: 77%
“…About 68.6% of breast cancer patients who were on chemotherapy had good family support, 65.7% used the problem-focused coping, 30.4% used the emotion-focused coping strategy, 52.0% experienced moderate anxiety, and only 2.0% experienced severe anxiety in the study conducted in southern India [ 8 10 ]. Therefore, this study aimed to identify stress coping strategies and their associated factors for breast cancer patients in TASH.…”
Section: Introductionmentioning
confidence: 99%
“…However, family support can represent either help or stress depending on the family’s expectations for BCS’s roles and reactions toward the disease ( Meacham et al, 2016 ; Hubbeling et al, 2018 ). For example, studies have found that BCS expressed feelings of sadness, embarrassment, decreased self-worth, and attractiveness ( Ashing-Giwa et al, 2004 ; Hu et al, 2021 ). Alternatively, felt embarrassed or anxious due to their body shape ( Bloom et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…BCS approached and understood life differently after having BC, which was one coping tool. Hu et al (2021) resulted that one of the coping strategies BCS had been the support from their communities or individuals external from the family.…”
Section: Introductionmentioning
confidence: 99%